Kilka uwag o prawnych formach działania administracji w zakresie dostępu do broni palnej - Mikowski, Rafał (E-Wydawnictwo. Prawnicza i Ekonomiczna Biblioteka Cyfrowa. Wydział Prawa, Administracji i Ekonomii Uniwersytetu Wrocławskiego, 2016)
In this article key issues related to access to firearms in Poland were discussed, taking into account the administrative and legal methods of regulation and current threats both in Poland and throughout the world. Selected issues concerning types of firearms, categories of permits for firearms, firearm registration obligations, conditions of storage of firearms or carrying of firearms are presented succinctly in the light of some form of administrative action. The law of 21 May 1999 on weapons and ammunition together with selected implementing acts was subjected to a synthetic analysis. In the light of these regulations, the leading role of the administrative decision on the subject of access to firearms and ensuring the safety of their use was discussed. Also the material-technical activities as those which play a complementary role in this matter were pointed out.
Keywords: material-technical activities; the permit for a firearm; firearm registration; administrative act